Windows Server Hybrid Administrator Associate (AZ-801) Cert Prep: 1 Secure Windows Server On-Premises and Hybrid Infrastructures. - McMillen, Robert (linkedin.com, 2023)
Learn the skills you need to know to prepare for the first domain of the Microsoft AZ-801 Configuring Windows Server Hybrid Advanced Services certification exam.